Estrategia didáctica “Inrac” para mejorar las actitudes de conservación medio ambientales en los alumnos del 6to grado de primaria de la I.E N°00925 Santa Isabel – Nueva Cajamarca - Alcalde Collantes, Osben (2010)
Today in day the concem for the environment is enormous; well, the governments of the Ameriuan countlies and from al! over the world they are propitiating studies for their conservation looking for mainly the change of the population's attitudes that that apparently should leave mainly for the childhood. For this reason, the present investigation denominated didactic Strategy INRAC lnvestigates he/she Reasons and it Acts to improve the half environmental conservation attitudes in the students of the Sixth Degree of the Primary Leve! ofthe I.E.N° 00925 Santa Isabel, New Cajamarca; it has traced their objectives guided to strengthen tl1e attitudes related with the world interest for the conservation of the atmosphere. This study you car justifies exactly for the relevancy of its realization in a time of climatic changes w11en it is necessary to promete the change of attitudes in the populations to bet for a rational use of the natura! means based in political of conserv.ation. Also for their practica! utility, slnce he/she intends to pro mote the environmental conservation by means of the development of learning activities that you/they involve the childhood like fundamental agent of change for the future generations. All tt:lis looking for to optimize the attitudes toward the conservation and protection of the environment and in that way to elevate the quality of lite and propiti,ating a better environmenta! future. The didactic strateg.y INRAC lnvestigates he/she Reasons and it Acts it was systematized keeping in m:ind the theory of the action reasoned according to FISHBEIN and AJZEN (1975) and the principies of the environmental education according to APCN (1996), besides other theoretical contributions that were good us as antecedents for the investigation. Based on the mentioned theories, he/she thought about the alternativa hypothesis in the following terms: lf the didactic strategy "INRAC" is applied, then they will improve the half environmental conservation attitudes significantly in the students of the Sixth Degree of the Primary Level of the I.E N° 00925 Santa Isabel - New Cajamarca. The population considerad for the study was conformad by the sections TO and B of the Sixth Degree of the I.E.N° 00925 Santa Isabel, New Cajamarca, of which the sample was e~tracted by means of the simple aleatory sampling be.ing as experime.ntal :grGQp tlle section To with 25 students between women and males. Also, the used investigation design was the design experimental pre with a single group. To the elected sample, he/she was administered a pre test to evaiuate the level of attitudes of half environmental conservation that the students possessed befare the application of the s.trategy; subsequently the sessions were developed proposed by the didactic strategy lf\JRAC he/she lnvestigates, he/she Reasoris and it Acts for the period of one month. After having culminated this period, the search test was administered that anowed to determine the effects taken place by the didactic strategy. With the obtained data, you proceeded to the analysis and respective interpretation of the same ones, be.ing demonstrated that the application of the didactic strategy INRAC lnvestigates, he/she Reasons and it Acts it improved the half environmental conservation attitudes significantly in tlle three components: cognitivo, emotional and conductual, promoting them from unfavorable attitudes to highly favorable attitudes in the students of Sixth Degree Leve! Primary of the Educational lnstítution N° 00925 Santa Isabel, New Caja marca.